Tyrosine 319, a newly identified phosphorylation site of ZAP-70, plays a critical role in T cell antigen receptor signaling. - Di Bartolo, V; Mège, D; Germain, V; Pelosi, M; Dufour, E; Michel, F; Magistrelli, G; Isacchi, A; Acuto, O (1999)
Following T cell antigen receptor (TCR) engagement, the protein tyrosine kinase (PTK) ZAP-70 is rapidly phosphorylated on several tyrosine residues, presumably by two mechanisms: an autophosphorylation and a trans-phosphorylation by the Src-family PTK Lck. These events have been implicated in both positive and negative regulation of ZAP-70 activity and in coupling this PTK to downstream signaling pathways in T cells. We show here that Tyr315 and Tyr319 in the interdomain B of ZAP-70 are autophosphorylated in vitro and become phosphorylated in vivo upon TCR triggering. Moreover, by mutational analysis, we demonstrate that phosphorylation of Tyr319 is required for the positive regulation of ZAP-70 function. Indeed, overexpression in Jurkat cells and in a murine T cell hybridoma of a ZAP-70 mutant in which Tyr319 was replaced by phenylalanine (ZAP-70-Y319F) dramatically impaired anti-TCR-induced activation of the nuclear factor of activated T cells and interleukin-2 production, respectively. Surprisingly, an analogous mutation of Tyr315 had little or no effect. The inhibitory effect of ZAP-70-Y319F correlated with a substantial loss of its activation-induced tyrosine phosphorylation and up-regulation of catalytic activity, as well as with a decreased in vivo capacity to phosphorylate known ZAP-70 substrates, such as SLP-76 and LAT. Collectively, our data reveal the pivotal role of Tyr319 phosphorylation in the positive regulation of ZAP-70 and in TCR-mediated signaling.